REDESAIN SARANA DAN FASILITAS PELABUHAN PERIKANAN SAMUDERA BITUNG - Mantiri, Yohanes Y.; Warouw, Fela (Jurnal Arsitektur DASENG, 2014)
Ocean Fishing Port of Bitung has a great influence for the local economy of Bitung and also to the North Sulawesi province. Included in one of the 6 largest fishing ports of Indonesia, because it has not only to the scope of services to domestic but to international as welll. But in terms of management and the procurement of port facilities, Ocean Fishing Port of Bitung is still lacking. Systems and facilities management of ocean fishing port is still not comply as ocean fishing port, both in terms of the circulation system, wherein the circulation for  production’s vehicles,publics and administration is narrow, in terms of total area, total area of ​​the port is still not comply the Ocean Fishing Port standards. From terms of the facility it still not well organized and optimal. This several aspects causes the performance and functionality of the ocean fishing port of Bitung not optimal. The chosen theme is "Application of Interlocking Concepts in Architecture" in the Redesign of  infrastructure and facilities Ocean Fishing Port of Bitung. Interlocking concept applied at macro(site) and the micro (building mass), to produce a new design with infrastructure and facilities of  Ocean Fishing Port that well organized, so that the performance and functionality of the ocean fishing port of Bitung can be optimal. Keywords: fishing port, bitung, interlocking